Gamzigrad, Serbien: Der spätantike Kaiserpalast Felix Romuliana und sein Umfeld - Škundrić, Jana; Wulf-Rheidt, Ulrike (e-Forschungsberichte des DAI, 2023)
As a part of the TOPOI Excellence Cluster in Berlin the immediate and wider hinterland of the late antique fortified palace of Felix Romuliana associated with the emperor Galerius (283–311 AD) was studied. Despite a long research tradition at the palace, there has been little study of its hinterland. In investigating the settlement patterns surrounding Felix Romuliana from prehistoric to mediaeval times important insights into the diachronic development of this micro-region were provided and led also to a new understanding of the historic and topographic framework of the role of the palace.